Association between leisure activities, anxiety, depression and well-being of older adults living in nursing homes in Slovakia - Sováriová Soósová, Mária (Magyar Gerontológia, 2022)
Engaging in leisure activities (LA) is associated with physical, psychological and social benefits leading to feelings of happiness, life satisfaction and successful ageing in older adults.